2010
DOI: 10.1063/1.3469827
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of mass fractal dimension and cluster size of silica in styrene butadiene rubber composites

Abstract: The morphology of the precipitated silica VN3 filled in styrene butadiene rubber was studied as a function of the volume fraction Φ by means of small-angle X-ray scattering experiments. The wide q-range of 0.008 nm(-1) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…[1] While the former are believed to be indivisible gatherings of elementary particles, the latter consist of clusters of weakly bounded aggregates that can be "broken" by applying mechanical stress, e.g. in nanocomposites, by "internal" mixing [2][3][4] or in solution via stirring [5] and sonication. [6,7] When loosely packed, these nano-architectured materials are essentially composed of air (>80%) [8][9][10][11][12] with typical pore sizes not exceeding 200 nm, making them excellent candidates for thermal insulation applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1] While the former are believed to be indivisible gatherings of elementary particles, the latter consist of clusters of weakly bounded aggregates that can be "broken" by applying mechanical stress, e.g. in nanocomposites, by "internal" mixing [2][3][4] or in solution via stirring [5] and sonication. [6,7] When loosely packed, these nano-architectured materials are essentially composed of air (>80%) [8][9][10][11][12] with typical pore sizes not exceeding 200 nm, making them excellent candidates for thermal insulation applications.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these particles as homogeneous spheres, the radius p R can be related with the radius of gyration Table 3 and Table 4. 15,19,20 . The main reason could be related to the fact that the pre-factors H [1][2][3][4] are not correlated among each other.…”
Section: Beaucage Analysismentioning
confidence: 99%
“…On the other hand, SAXS data is highly representative due to the macroscopic sample size that is probed but these data have to be fitted with a suitable model function in order to obtain structural information. Several structural studies in SBR and NR filled compounds have been undertaken by different groups [15][16][17][18][19][20] . However, due to the complex hierarchical morphologies associated to the fillers and their diversity of sizes, to date there is no analytical model consistently describing the structure at all length scales.…”
Section: Introductionmentioning
confidence: 99%
“…The latter result is, however, surprising on first glance. We will try to explain it by using scattering studies of the average cluster size in the nanometer range [7]. There, it was observed that the average cluster size decreases with increasing particle fraction Φ due to the influence of enhanced mechanical shear forces during the mixing process.…”
Section: Discussionmentioning
confidence: 97%
“…In general, there is a multitude of possible reasons causing the different material responses to an external perturbation. It ranges from the case of well dispersed nanoparticles, where different interaction potentials between the polymer and the surface may be responsible for the particular response of the composite [1][2][3][4][5][6], up to particle dominated behavior in the case of very high particle fractions and hierarchically structured particles [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%